2021
DOI: 10.1016/j.scitotenv.2020.142289
|View full text |Cite
|
Sign up to set email alerts
|

Environmental virus detection associated with asymptomatic SARS-CoV-2-infected individuals with positive anal swabs

Abstract: In the fight against the outbreak of COVID-19 in China, we treated some asymptomatic infected individuals. This study aimed to detect pathogens in biological and environmental samples of these asymptomatic infected individuals and analyse their association. Using a cross-sectional study design, we collected biological and environmental samples from 19 patients treated in the isolation ward of Nanjing No.2 Hospital. Biological samples included saliva, pharyngeal swabs, blood, anal swabs, and exhaled breath cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Of interest, a recent Chinese study investigating asymptomatic carriers of the SARS-CoV-2 virus in an isolation ward, showed that all carriers had positive anal swabs for the virus. Interestingly, among 96 different environmental sampling in this ward, only three samples were positive for the virus and included a cell phone, a cell phone shelf and a bedside rail 17 . Common fecal-derived microbes are frequently found on mobile phones such as Acinetobacter , Enterococci species 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, a recent Chinese study investigating asymptomatic carriers of the SARS-CoV-2 virus in an isolation ward, showed that all carriers had positive anal swabs for the virus. Interestingly, among 96 different environmental sampling in this ward, only three samples were positive for the virus and included a cell phone, a cell phone shelf and a bedside rail 17 . Common fecal-derived microbes are frequently found on mobile phones such as Acinetobacter , Enterococci species 5 .…”
Section: Discussionmentioning
confidence: 99%
“…It had been previously hypothesised that mobile phones should be considered as a ‘Trojan Horse’ for SARS-CoV-2 virus and contributing to the transmission and spread of the disease globally 4 . Such phones would be contaminated because of viral shedding from COVID-19 sufferers either by faecal material deposition on phones, and/or contact of phones with uncleaned virally infected hands and/or patient’s deposition of high loads of droplet rich viruses during calls on mobile phones 7 . Indeed, a recent article demonstrated clearly that viruses (including SARS-CoV-2) can survive on glass surfaces (e.g., mobile phones) and polymer plastic surfaces (e.g., bank notes) for extended periods [up to 28 days in comparison to the previous estimated survival time of 14 days] 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Whilst individuals might or might not wash their hands when exiting www.nature.com/scientificreports/ restrooms, their phones used in toilets are likely to be contaminated either due to the flushing plume effect or simply by contact with yet un-washed hands. Coincidentally, a recent study working on the SARS-CoV-2 virus pandemic, showed that coronaviruses were retrieved from anal source samples belonging to asymptomatic COVID-19 positive patients and such viruses have been detected on mobile phones 7 . It had been previously hypothesised that mobile phones should be considered as a 'Trojan Horse' for SARS-CoV-2 virus and contributing to the transmission and spread of the disease globally 4 .…”
Section: Antibiotic Resistance Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant concern regarding SARS-CoV-2 is its transmission through aerosols and direct contact [5], which is associated with environmental conditions and human behavior [6,7]. However, several studies reported a correlation between the number of daily confirmed cases of COVID-19 and the environmental viability of the virus [8,9]. Therefore, the spread control of SARS-CoV-2 is a global challenge, and the evidence of its circulation on the inanimate surfaces are important to reinforce public health measures to limit transmission of the virus [5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%